The Influence of Online Service Quality on Consumer Satisfaction of Hijama Patients in Sidoarjo - Mochamad Samsi; Putra, Iswidana Utama; Widhi Yanti, Dyah Agustin (FAKULTAS EKONOMI UNIVERSITAS MAARIF HASYIM LATIF, 2024)
This study aims to examine the impact of perceived service quality, online customer reviews, and online customer ratings on consumer satisfaction with online services. The hypothesis tested is that these variables significantly affect customer satisfaction. A quantitative approach was used with data collected through a structured questionnaire distributed to 60 online service users selected through purposive sampling. Multiple linear regression analysis was used to assess the relationship between variables. The results show that perceived service quality has the strongest positive influence on consumer satisfaction, followed by online customer ratings and reviews. The findings emphasize the importance of improving service quality and managing customer feedback online to increase satisfaction. This research contributes new knowledge about consumer behavior in online platforms by highlighting the interrelationships between service quality, customer reviews, and ratings. The originality of this research lies in its examination of how these factors collectively affect consumer satisfaction, providing valuable insights for businesses aiming to improve their online services and customer relationships..